Evaluating the effects of climate on dengue cases in Kelantan - Masrani, Afiqah Syamimi (2020)
Introduction: Dengue remains endemic in Kelantan despite considerable investment in vector control activities. Climate plays an integral role in affecting the magnitude of dengue incidences and has been integrated into some local Early Warning and Response System for dengue. In order to enhance the proactive usage of climate factors for a state-specific, time-based estimation of dengue incidence in Kelantan, the effects of climate on dengue cases needs to be evaluated. Objective: The study aims to evaluate the effects of climate on dengue cases in Kelantan from 2016 to 2018 by analysing the trend of dengue cases in Kelantan, mapping of incidence rate and spatial clustering of dengue by district, and estimating the effects of temperature, rainfall and wind speed on dengue cases in Kelantan. Methodology: The study design uses a retrospective secondary data review of daily dengue case obtained from the eDengue system and daily minimum temperature, maximum temperature, mean temperature, cumulative rainfall and average wind speed obtained from Kota Bharu Weather station from the year 2016 to 2018. Universal sampling of the 10,645 data obtained was applied following sample size calculation of 10,704. The ArcMap application was used to analyse and map the dengue incidence rate and spatial clustering of dengue cases through hotspot analysis. The effect of climate on dengue cases was analysed by using a Poisson generalized additive model in the “mgcv” package of R software. Results: There was an average of 9.8 dengue cases daily in Kelantan. A cyclical pattern was observed with peak cases occurring between April and October annually. The dengue incidence rate shows a reducing trend with the highest incidence and significant hotspot identified being in Kota Bharu district. The maximum temperature, mean temperature, rainfall, and wind speed shown significant non-linear effect on dengue incidence. The highest peak of dengue incidence found at the maximum temperature between 31.5˚C to 34˚C, the mean temperature between 23˚C to 26˚C, rainfall between 20mm to 30mm, and wind speed between 0 m/s to 2 m/s. Conclusion: There is a limited window of opportunity before the start of the intermonsoon period for enhanced vector control activities in order to reduce the magnitude of dengue cases. The changing geography of spatial clusters should also be considered for a targeted approach. Monitoring of climate variables through interagency collaboration between the Malaysian Meteorology Department and the Ministry of Health Malaysia provides an improved early warning system for dengue.